Imaging displacement and strain in the medial gastrocnemius muscle during ankle-joint motion using 2D-ciné DENSE MRI - Lawson, Andrew James (Division of Radiology, 2015)
Skeletal muscle structure has been defined on both macro and microscopic levels by gross dissection, light- and electron-microscopy. The basic physiological building blocks involve the electromechanical coupling between interlinking actin and myosin fibres. Detailed intramuscular behaviour during contraction can be clearly defined when examining a single isolated muscle. However, there are few areas in the human body where single muscles act independently to affect motion. This thesis attempts to address the compounded effect that muscles have on each other, while working synergistically in a group, such as the calf muscle.